2017
DOI: 10.1111/aas.12861
|View full text |Cite
|
Sign up to set email alerts
|

Early treatment with isoflurane attenuates left ventricular dysfunction and improves survival in experimental Takotsubo

Abstract: Early treatment with isoflurane attenuates the LV akinesia and improves survival in experimental TS. Isoflurane sedation in patients at risk of developing Takotsubo syndrome could be a subject for future studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Early treatment with isoflurane reduced left ventricular dyskinesia and improved the survival rate of experimental TTS, while H 2 S reduced ROS formation by reducing NADPH oxidase [202,203]. GPER, azelnidipine, Tempol and amlodipine also played a protective role for TTS [153,186,204,205].…”
Section: Animal Models and Mechanistic Studiesmentioning
confidence: 95%
“…Early treatment with isoflurane reduced left ventricular dyskinesia and improved the survival rate of experimental TTS, while H 2 S reduced ROS formation by reducing NADPH oxidase [202,203]. GPER, azelnidipine, Tempol and amlodipine also played a protective role for TTS [153,186,204,205].…”
Section: Animal Models and Mechanistic Studiesmentioning
confidence: 95%
“…Since experiments in a TTS rodent model with catecholamine-triggered TTS revealed that isoflurane anesthesia exerted a protective effect for development of LV dysfunction [ 126 , 127 ], it would be of great interest to evaluate even in a limited cohort this therapy’s impact in human TTS.…”
Section: Future Therapeutic Options For Ttsmentioning
confidence: 99%
“…), isoflurane (an anaesthetic agent) was recently found to be effective both in the prevention and attenuation of TTC-induced LV dysfunction in experimental studies. 58,59 However, further studies are still warranted to discover novel agents with preventive features and disease-specific actions (targeted therapy) in the setting of TTC. Unfortunately, there exists no specific targeted therapy for the management of acute and/or residual LV dysfunction in the setting of TTC, and the use of supportive measures is generally indicated as the…”
Section: Management Of Left Ventricular Dysfunctionmentioning
confidence: 99%